Dampak Asesmen Formatif terhadap Pengembangan Karakter Disiplin dalam Pembelajaran Sekolah Dasar - Atiyah Atiyah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the impact of formative assessment on the development of elementary school students' disciplinary character. Formative assessment is an assessment that is carried out continuously to provide feedback to students in order to improve their learning process. In the context of character education, especially discipline, formative assessment not only functions as an academic evaluation tool, but also as an instrument for forming attitudes. This study uses a qualitative approach with a case study method in one of the public elementary schools in Central Java. Data were collected through classroom observations, interviews with teachers, and assessment documentation. The results of the study indicate that the implementation of formative assessment consistently has a positive impact on the habituation of student discipline behavior, such as punctuality in collecting assignments, regularity in taking notes, and readiness to participate in learning. The feedback provided by teachers in formative assessment encourages students to reflect on and improve their learning attitudes. This study recommends the integration of formative assessment as part of a character-based learning strategy, especially in strengthening disciplinary values ​​from an early age.